Mechanical characterization of the AlSi9Cu3 cast alloy under distinct stress states and thermal conditions. (July 2019) - Gain, S.; Silva, T.E.F.; Jesus, A.M.P.; Cavaleiro, A.; Rosa, P.A.R.; Reis, A.
Highlights: The AlSi9Cu3 alloy has been investigated by mechanical testing. Temperature and multiaxial stress fields influence on elastoplastic and fracture behaviours analysed. Fracture strains were identified with respect to negative to positive stress triaxiality rage. The Drucker-Prager model was suitable to model the mechanical behaviour. Special multiaxial specimens were proposed and succesfully validated the constitutive model. Abstract: This paper presents the results of several mechanical tests aiming at characterizing the constitutive behaviour of the AlSi9Cu3 cast alloy, covering different temperatures and stress fields, including tensile and compressive tests of smooth and notched specimens as well as combined shear/tension and shear/compression with special designed specimens. The Johnson-Cook model was able to correlate the flow stress under quasi-static uniaxial compression, including thermal effects. However, under tension the yield stress does not reduces monotonically and gradually with temperature, which impedes the application of Johnson-Cook model for positive triaxialities. At room temperature, the AlSi9Cu3 alloy shows significant asymmetrical tensile and compressive behaviours requiring a plasticity model sensitive to the stress triaxiality such as the Drucker-Prager. As regards the ductility limits of the material, different data was analysed to generate fracture loci for the material where equivalent fracture strains were plotted against the stress triaxialities. The calibrated Drucker-Prager constitutive model together with a damage approach based on the fracture loci generated was successfully verified using test data from specimens loaded under combined shear/tension or shear/compression. The AlSi9Cu3 cast alloy exhibits a sharp reduction in ductility between the negative stress triaxiality cut-off and −0.1, keeping at low levels above this triaxiality value.